2012
DOI: 10.1007/978-3-642-33197-8_12
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Like Me in This: User Embodiment Preferences for Companion Agents

Abstract: Abstract. We investigate the relationship between the embodiment of an artificial companion and user perception and interaction with it. In a Wizard of Oz study, 42 users interacted with one of two embodiments: a physical robot or a virtual agent on a screen through a role-play of secretarial tasks in an office, with the companion providing essential assistance. Findings showed that participants in both condition groups when given the choice would prefer to interact with the robot companion, mainly for its gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…This also follows for simulated work, for example, that people may prefer to interact with [22,30] or play a game with a real robot instead of a simulated one [20]. Much of this may simply be the novelty factor of robots, where people enjoy or prefer interacting with new and exciting technologies such as robots.…”
Section: Related Work and Backgroundmentioning
confidence: 90%
“…This also follows for simulated work, for example, that people may prefer to interact with [22,30] or play a game with a real robot instead of a simulated one [20]. Much of this may simply be the novelty factor of robots, where people enjoy or prefer interacting with new and exciting technologies such as robots.…”
Section: Related Work and Backgroundmentioning
confidence: 90%
“…Since this is not at present an uncontroversial assertion, we first briefly consider and justify the role of robot embodiment itself. A range of efforts have focused on the use of simulated or virtual agents and avatars, in addition to physically embodied robotic devices, with some efforts to combine the two (Segura, Kriegel, Aylett, Deshmukh, & Cramer, 2012). In addition to the clear advantage that physical robots have in terms of real world interaction and manipulation (Stiehl et al, 2009;Shibata, 2011), regarding the difference between the embodiment types, there are three aspects that indicate some (potential) advantage is conferred by the presence of a physical robot.…”
Section: Introductionmentioning
confidence: 99%
“…Also, higher degrees of freedom in the robot's movement led participants to report the robot was more indicative during the interaction, in which the participants explained the use of household objects to the robot (Fischer et al, 2012). Segura et al (2012) found that people preferred to interact with a robotic agent than a virtual agent because of the robot's physicality, but their overall perceptions of the surrogates were not different-they concluded that the users focused more on the surrogate's behaviors in the task-based context. Rodriguez-Lizundia et al used an interactive bellboy robot to evaluate engagement and comfort with different robot designs and behaviors.…”
Section: Physicality and Gesturingmentioning
confidence: 99%